DISCLOSURE OF MEDICAL ERROR - Shaikh, Kiran; Lalani, Sharifa Bashir (Journal of Ayub Medical College Abbottabad, 2011)
With the advancement of medical sciences, lives are being prolonged and practice of medicine is considered an art and no longer as science. ’˜To Err is Human Report’ has been released and gives data of medical errors in United States which opened people’s eyes but there is grieving need that health professional in Pakistan also report the medical errors. Medical errors are common, costly, and often preventable. This could only happen when health professional are trained and made aware to report the errors. Evidences shows that full and honest disclosure of error and restitution are factors that may lead to significant improvement in responsibility of medical cases. Keywords: medical error, honest disclosure, patient safety